Long-term treatment with selective PI3Kδ inhibitor leniolisib in adults with activated PI3Kδ syndrome - Rao, V Koneti; Kulm, Elaine; Grossman, Jennifer; Buchbinder, David; Chong, Hey; Bradt, Jason; Webster, Sharon; Šedivá, Anna; Dalm, Virgil A; Uzel, Gulbu (Blood advances, 2024)
Activated phosphoinositide 3-kinase delta (PI3Kδ) syndrome (APDS) is an inborn error of immunity that manifests as immune deficiency and dysregulation; symptoms include frequent infections and lymphoproliferation. In our dose-finding and phase 3 placebo-controlled trials, treatment with the selective PI3Kδ inhibitor leniolisib reduced lymphoproliferation and normalized lymphocyte subsets. Here, we present 6 years of follow-up from the 6 adult patients in the original dose-finding trial receiving leniolisib. We used data from the ongoing open-label extension study, which was supplemented at later time points by investigators, including health-related quality of life (HRQoL) assessed through a clinician-reported questionnaire. We observed improvements in HRQoL: 5 of 6 patients experienced an increase in physical capabilities and socialization, and a decrease in prescribed medications. Immune subsets improved in all patients: mean transitional B-cell levels decreased from 38.17% to 2.47% and the CD4:CD8 T-cell ratio normalized to 1.11. Manifestations seen before and within the first year of leniolisib exposure, such as infections and gastrointestinal conditions, attenuated after year 2, with few new conditions emerging out to year 6. Thrombocytopenia or lymphopenia remained present in half of patients at year 6. Of 83 adverse events through year 5, 90.36% were grade 1; none were grade 4/5 nor deemed leniolisib related. Collectively, we saw an enhancement in HRQoL as well as durable changes in lymphocyte subsets and clinical manifestations, further supporting the use of leniolisib as a long-term therapeutic option for the treatment of APDS. This trial was registered at www.ClinicalTrials.gov as #NCT02859727.
Keywords: Humans; inhibitory proteinkinas; lidé středního věku; Quality of Life; Phosphoinositide-3 Kinase Inhibitors; Female; dospělí; výsledek terapie; inhibitory fosfoinositid-3-kinasy; lidé; Class I Phosphatidylinositol 3-Kinases; kvalita života; Primary Immunodeficiency Diseases; Adult; Protein Kinase Inhibitors; ženské pohlaví; Male; Middle Aged; Treatment Outcome; fosfatidylinositol-3-kinasy třídy I; mužské pohlaví; primární imunodeficience